1969
DOI: 10.1177/002383096901200202
|View full text |Cite
|
Sign up to set email alerts
|

On the Complex Regulating the Voiced-Voiceless Distinction I

Abstract: An investigation is described of the perceptual and acoustical differences between voiceless and voiced consonants in Dutch. The experiments reported included synthesized, normal and whispered speech. The results are compared with those found in the literature for other languages. Parallels between the results of the various investigations could be established, although quantitative differences apply to different languages. It is shown that a number of perceptual and acoustical cues are present, such as: soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…Vocal fold vibration has been established as another major cue to the fortis-lenis distinction in fricatives (e.g., Fischer-J0rgensen 1963 for German; Slis & Cohen 1969a, 1969bvan den Berg & Slis 1985, Kissine et al 2003 for Dutch, but see Jessen 1998 for a description of [voice] as a feature different from fortis/lenis). In general, /v, z/ are produced with vocal fold vibration, whereas /f, s/ are not.…”
Section: Phonetic Correlates O F the Fortis-lenis Contrastmentioning
confidence: 99%
“…Vocal fold vibration has been established as another major cue to the fortis-lenis distinction in fricatives (e.g., Fischer-J0rgensen 1963 for German; Slis & Cohen 1969a, 1969bvan den Berg & Slis 1985, Kissine et al 2003 for Dutch, but see Jessen 1998 for a description of [voice] as a feature different from fortis/lenis). In general, /v, z/ are produced with vocal fold vibration, whereas /f, s/ are not.…”
Section: Phonetic Correlates O F the Fortis-lenis Contrastmentioning
confidence: 99%
“…As early as the 1970s it has been shown that the same phonetic phenomenon can be related to several different acoustic features (Repp, 1981;Slis & Cohen, 1969). Also, the information carried by some features, such as pitch or formants, is encoded in dynamical changes over time, rather than as fixed-length sequences of scalars that reflect the feature value at crucial points, such as the beginning and the end of a segment.…”
Section: Introductionmentioning
confidence: 99%
“…Other significant cues were the duration and power of the burst. For intervocalic obstruents, presence or absence of vocal-fold vibration ͑Slis and Cohen, 1969b; Slis and Van Heugten, 1989͒, closure duration for stops ͑Kuijpers, 1996; Slis and Cohen, 1969a͒, and frication duration for fricatives ͑Slis and Van Heugten, 1989͒ have been shown to influence the perception of voicing. For intervocalic two-obstruent sequences, presence or absence of vocal-fold vibration during the closure of the two obstruents is the most important cue ͑Van den Berg, 1989͒.…”
Section: Introductionmentioning
confidence: 99%